2015
DOI: 10.5414/cp202226
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus therapy causes hepatotoxicity in patients with a history of liver disease

Abstract: Results indicate that tacrolimus may have a higher risk of inducing liver injury in Korean patients with a history of liver disease and may require close monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[16][17][18] Wuzhi capsule, a traditional Chinese medicine (registration number in China: Z10983013), is often prescribed to alleviate the hepatotoxicity of tacrolimus in China. [19][20][21] Wuzhi capsule has been reported to increase tacrolimus exposure, leading to further dose reduction of approximately 50% or more. 22,23 Pharmacokinetic studies 24,25 have showed that co-treatment with Wuzhi capsule can reduce the clearance rate, peak concentration, and peak time delay of tacrolimus.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Wuzhi capsule, a traditional Chinese medicine (registration number in China: Z10983013), is often prescribed to alleviate the hepatotoxicity of tacrolimus in China. [19][20][21] Wuzhi capsule has been reported to increase tacrolimus exposure, leading to further dose reduction of approximately 50% or more. 22,23 Pharmacokinetic studies 24,25 have showed that co-treatment with Wuzhi capsule can reduce the clearance rate, peak concentration, and peak time delay of tacrolimus.…”
Section: Introductionmentioning
confidence: 99%
“…It has a narrow therapeutic window so that therapeutic drug monitoring is recommended for the patients receiving tacrolimus. Furthermore, long‐term use of tacrolimus can cause liver damage such as elevation of alanine aminotransferase (ALT) and total bilirubin level . In China, a traditional Chinese medicine named Wuzhi is often prescribed to patients to alleviate the hepatotoxicity of tacrolimus .…”
mentioning
confidence: 99%
“…It indicates that Fk506 is most likely to cause impaired liver function in this event. And according to Ko reports [12], patients who had underlying liver disease should closely monitor the changes in liver function when treated with FK506.…”
Section: Hepatotoxicitymentioning
confidence: 99%